(untitled) (Journal of Management and Social Sciences, 2023)
Organizations throughout the world are experiencing a talent shortage in this competitive era, thus placing pressure on human resource managers to strategically implement an effective succession planning that is capable of attracting, fostering, and guaranteeing the retention of the greatest talents in the workplace. This study examines the impact of effective succession planning on the retention of employees in Multi – Trex Integrated Food Plc, Lagos. This was with the use of structured questionnaire. The employed descriptive statistics included simple percentages and tables, while inferential statistics adopted regression analysis. The findings of the study showed a significant impact of (i) mentorship on the employee’s retention; and (ii) coaching on the employee’s retention in the organization. The study concluded that there was significant impact of effective succession planning on employees’ retention in Multi – Trex Integrated Food Plc, Lagos. The study recommended the creation of regulations that allow employees to be easily identified and selected while streamlining succession planning to the corporate goals and objectives. Keywords Employee retention, succession planning, talent management, organization